Triple-negative bilateral synchronous infiltrating lobular cancer in an elderly male: A rare case report - Sathiah, Prasath; Gochhait, Debasis (Tropical Journal of Pathology and Microbiology, 2020)
Breast malignancy in males is rare, because of the absence of lobules. Here we are presenting the case of 65 male patients presented with bilateral breast enlargement. On examination also shows a bilateral pleural effusion. Sonomammogram shows features of gynecomastia. A bone scan shows multiple skeletal metastases involving all over the body. Trucut biopsy from both breasts shows tumor with features of infiltrating lobular carcinoma. Immunohistochemistry revealed this tumor as triple-negative. Plural fluid cytology examination shows evidence of metastasis adenocarcinoma deposits.